Mapping the specialized educational care of hearing-impaired students during the pandemic in brazilian minicipalities (Research, Society and Development, 2021)
This paper aims to disclose the mapping that we did about how the school attendance of deaf students in kindergarten and elementary school I and II has been happening in Brazilian municipalities in this period of pandemic caused by the coronavirus. We used a descriptive, quantitative methodology with a questionnaire with closed and open questions that consisted in tracing the profile of the teachers, quantifying the students, relating the resources that are being used, checking the interaction of these students and their families with the schools, among other issues. With these data in hand, we outlined the current situation, identified the main difficulties, and described some strategies that teachers have been using with the intention of improving the specialized educational service for people with hearing impairments. We conclude that there is still much to be developed in the specialized educational service for people with hearing impairment and only the actors, directly involved in the educational and social process of this public, will be able to change the reality described here.